2009
DOI: 10.1007/s00284-008-9270-1
|View full text |Cite
|
Sign up to set email alerts
|

An Endophytic Taxol-Producing Fungus from Taxus media, Cladosporium cladosporioides MD2

Abstract: Fermentation processes using taxol-producing fungi other than Taxus spp. may be an alternative way to produce taxol, which is an important antitumor agent used widely in the clinic setting. In this study, a taxol-producing endophytic fungus strain MD2 was isolated from the inner bark of Taxus media. Strain MD2 produced taxol when grown in potato dextrose liquid medium. The fungal taxol-which was analyzed by ultraviolet, high-performance liquid chromatography and mass spectrometry-was shown to be identical to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(64 citation statements)
references
References 10 publications
3
59
1
1
Order By: Relevance
“…Several other groups soon confirmed the findings in this ground-breaking publication and provided additional supporting evidence (Flores-Bustamante et al 2010). Microbial Taxol and taxane biosynthesis was found in several different genera of fungi, including Alternaria, Aspergillus, Cladosporium, Fusarium, Monochaetia, Pestlotia, Pestalotiopsis, Pithomyces, Penicillium and Xylaria, which were isolated from yew and non-Taxus plants (FloresBustamante et al 2010;Strobel et al 1996;Soca-Chafre et al 2011;Zhang et al 2009;Zhao et al 2009;Hoffman 2003). Recently, several reports have been published claiming that endophytic fungi contain genes previously identified in Taxus spp.…”
Section: Introductionsupporting
confidence: 55%
“…Several other groups soon confirmed the findings in this ground-breaking publication and provided additional supporting evidence (Flores-Bustamante et al 2010). Microbial Taxol and taxane biosynthesis was found in several different genera of fungi, including Alternaria, Aspergillus, Cladosporium, Fusarium, Monochaetia, Pestlotia, Pestalotiopsis, Pithomyces, Penicillium and Xylaria, which were isolated from yew and non-Taxus plants (FloresBustamante et al 2010;Strobel et al 1996;Soca-Chafre et al 2011;Zhang et al 2009;Zhao et al 2009;Hoffman 2003). Recently, several reports have been published claiming that endophytic fungi contain genes previously identified in Taxus spp.…”
Section: Introductionsupporting
confidence: 55%
“…Chaetomella raphigera Terminalia arjuna [227] Cladosporium cladosporioides T. media [228] Cladosporium oxysporum Moringa oleifera [229] Cladosporium tenuissimum T. chinensis [223] Colletotrichum gloeosporioides Colletotrichum sp.…”
Section: T Chinensis [223]unclassified
“…67 Cladosporium cladosporoides, an endophyte of the Taxus media tree, produced 800 μg l − 1 of taxol. 68 Metarhizium anisopiliae H-27, isolated from the tree Taxus chinensis, yielded 846 μg l − 1 . 69 Although a review of taxol production by endophytic fungi indicated that strain improvement had resulted in levels of only 0.4-1.0 mg l − 1 , 70 it was reported that another fungus, Alternaria alternate var.…”
Section: Antineoplastic Drugsmentioning
confidence: 99%